SISTEM INFORMASI INVENTORY ALAT KESEHATAN PADA PT TAISHAN ALKES INDONESIA BERBASIS WEB - Hari Gunawan; Bobi Agustian (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
Information system inventory Medical deviceat PT. Taishan Alkes Indonesia is currently still using it manually, namely by recording books and copied using Microsoft Excel. thus causing errors in recording medical device data, both incoming and outgoing medical devices causing difficulties in finding available stock data. The purpose of this study is to provide convenience in processingdata inventory medical deviceso as to minimize errors in data input, data loss, save time and make it easier to find available stock data. With the existence of this web-based application, it can overcome problems in processing data on the safety equipment at PT. Taishan Alkes Indonesia because the data is well organized. This system is designed using the codeigniter framework and MySQL programming as the database.